Süleymaniye Kütüphanesi Yazma Bağışlar 5879’daki Mecmû’a-yı Eş’âr 1a-100a (inceleme – çeviriyazılı metin – diliçi çeviri) - Tek, Buse Nur (My University, 2020)
Çalışmamız, “Süleymaniye Kütüphanesi Yazma Bağışlar 5879” numarada kayıtlı olan bir şiir mecmuasının 1a-100a varaklarının çeviriyazı metninden ve diliçi çevirisinden oluşmaktadır. Bu varaklar arasında gazeller ve musammatlar yer almaktadır. Yazmada bulunan şiirler dîvânı yayınlanmış bir şaire ait ise dîvândaki yerleri belirtilmiş ve farklılıklar dipnotta gösterilmiştir.Çalışılan varak aralığındaki bazı şairlerin mahlaslarına ulaşılamamıştır. Bu mahlassız şairler ile birlikte 24 şairin toplam 131 şiiri bulunmaktadır. Genel olarak yazmada gazeller yer almaktadır. Çalışma, giriş, çeviriyazılı metin ve sonuç bölümlerinden oluşmaktadır.

Our dissertation consists of the transcription and linguistic translation of the 1a-100a papers of a poem collection registered in “Suleymaniye Library Writing Donations 5879”. These papers include lyric poems and musammats. If the poems in the collection belonged to a poet whose diwan was published, their place in the diwan was indicated and the differences were shown in the footnote.The takhallus of some poets in the studied paper range was not found. Along with poets without a takhallus, 24 poets have a total of 131 poems. Generally, there are lyric poems in the poem collection. The study consists of introduction, translation text and conclusion sections.
Keywords: divan; diwan; gazel; History and criticism; lyric poems; mecmua; poets; şair poem collection; Tarih ve eleştiri; Turkish literature; Türk edebiyatı